Greek Vases: Images, Contexts and Controversies : Proceedings of the Conference sponsored by The Center for the Ancient Mediterranean at Columbia University, 23-24 March 2002 - Marconi, Clemente (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
This volume deals with Greek painted vases, exploring them from various methodological points of view and moving beyond the traditional focus on connoisseurship and style. The volume, which represents the proceedings of an international conference sponsered by the Center for the Ancient Mediterranean at Columbia University, is an effort to exploit the immense richness of these vases by using them to study general cultural history.